Caries Experience and Knowledge About Oral Health Importance Among Children with Congenital Heart Diseases in Kosovo - Aida Rexhepi; Blerta Latifi-Xhemajli; Teuta Kutllovci; Shqiprim Bajrami; Dafina Ahmeti (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the dental health of children with Congenital Heart Diseases (CHD) and to evaluate the parents' knowledge of the importance of oral health and the risk of Bacterial Endocarditis. Material and Methods: This research included 140 children divided into the study group (80 children with CHD) and the control group (60 healthy children). The children were from different parts of Kosova, aged between 3-15. The parents were asked to complete a questionnaire containing demographic data (age and gender), general and special medical history (CHD types), knowledge about oral health importance and risk of bacterial endocarditis, and data about the daily oral hygiene child. The caries experience was reported using the DMFT/dmft index. Results: The average value of the dmft index was 6.7 for the study group and 5.62 for the control group, while the average value of DMFT index for the study group was 4.1, and for the control group was 3.47 (p>0.05). About 68.7% of parents of children with CHD were informed about their risk during dental interventions. However, knowledge was insufficient about the importance of oral health and dental prophylactic measures once only 32.7% of them were aware of those measures. Conclusion: No difference was observed between healthy and CHD children in caries experience and frequency of daily tooth brushing. Our findings provide evidence of a lack of knowledge about the importance of oral health and dental prophylactic measures among parents with CHD children.